2015
DOI: 10.1590/0074-02760150284
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Trypanosoma cruziexposure in domestic dogs from a rural community in Panama

Abstract: Chagas disease, caused by Trypanosoma cruzi infection, is a zoonosis of humans, wild and domestic mammals, including dogs. In Panama, the main T. cruzi vector is hodnius pallescens, a triatomine bug whose main natural habitat is the royal palm, Attalea butyracea. In this paper, we present results from three T. cruzi serological tests (immunochromatographic dipstick, indirect immunofluorescence and ELISA) performed in 51 dogs from 24 houses in Trinidad de Las Minas, western Panama. We found that nine dogs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
0
21
0
2
Order By: Relevance
“…Moreover, Saldaña et al [25] reported dogs in a rural location in Panama, were 11.6 times more likely to become infected if Attalea butyracea palms were present in the peridomicile. The effectiveness of vector control strategies could increase by considering the flying ability of triatomine bugs [15] and recognizing the role that palm-house proximity plays in house infestation and re-infestation after control strategies [23, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Saldaña et al [25] reported dogs in a rural location in Panama, were 11.6 times more likely to become infected if Attalea butyracea palms were present in the peridomicile. The effectiveness of vector control strategies could increase by considering the flying ability of triatomine bugs [15] and recognizing the role that palm-house proximity plays in house infestation and re-infestation after control strategies [23, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In outbreaks, particularly in Argentina, where Chagas' disease is transmitted by T. infestans, dogs and cats represent domestic reservoirs of T. cruzi infection (Cardinal et al, 2007). Levels of canine seroprevalence to T. cruzi are high in 15 countries and vary from 8 to 50% across various surveys, which are often conducted using different techniques (Barbabosa-Pliego et al, 2011;Berrizbeitia et al, 2013;Chikweto et al, 2014;Tenney et al, 2014;Alroy et al, 2015;Gürtler & Cardinal, 2015;Saldaña et al, 2015). Dogs should be prevented from becoming infected by restraining their access to ecosystems that feature vector bugs.…”
Section: Discussionmentioning
confidence: 99%
“…In Panama, there are 10 triatomine bug species that are T. cruzi vectors. However, only two species, Triatoma dimidiata and Rhodnius pallescens, are associated with Chagas disease transmission to human populations in this region; of these, R. pallescens is Panama's dominant vector (16,17). R. pallescens' preferred habitat, the A. butyracea palm (Figure 1), is a dense-crowned species in the subtribe Attaleinae that ranges from Mexico to western Amazonia (6,9).…”
Section: Background: Chagas Disease In Panamamentioning
confidence: 99%
“…A. butyracea palms in secondary growth regions are more likely to be infested with Chagas disease vectors (8), and, when initial deforestation occurs as a result of human settlement and agriculture, inherently more likely to exist in close proximity to human establishments (9,10). This close proximity of households to Attalea spp palms is hypothesized to increase risk of Chagas disease transmission in humans (11)(12)(13)(14)(15)(16) and has been shown, in one study, to increase risk in domestic canine populations (17).…”
Section: Introductionmentioning
confidence: 99%